2014
DOI: 10.1167/iovs.14-15458
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Molecular Diagnosis of a Large Cohort of Japanese Retinitis Pigmentosa and Usher Syndrome Patients by Next-Generation Sequencing

Abstract: By screening a large cohort of patients, this study catalogued the genetic variations involved in RP and Usher syndrome in a Japanese population and highlighted the different distribution of causative genes among populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
116
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 149 publications
(127 citation statements)
references
References 32 publications
7
116
4
Order By: Relevance
“…36,[39][40][41][42][43][44][45][46] Electroretinography is consistent with a severe generalized rod-cone dysfunction, typical for RP, and may have an electronegative pattern. 47 Only two cases of recessive retinal dystrophies due to NRL mutations have been reported to date (Table).…”
Section: Discussionmentioning
confidence: 99%
“…36,[39][40][41][42][43][44][45][46] Electroretinography is consistent with a severe generalized rod-cone dysfunction, typical for RP, and may have an electronegative pattern. 47 Only two cases of recessive retinal dystrophies due to NRL mutations have been reported to date (Table).…”
Section: Discussionmentioning
confidence: 99%
“…5 All patients underwent comprehensive ophthalmological examinations, including measurement of the best-corrected visual acuity (BCVA) using a decimal visual acuity chart (Landolt chart), indirect ophthalmoscopy, slit-lamp biomicroscopy, SD-OCT (Spectralis HRA+OCT, Heidelberg Engineering, Heidelberg, Germany); mean deviation (MD) value at baseline calculated using a Humphrey field analyzer (HFA; 10-2 SITA Standard Program; Carl Zeiss Meditec, Jena, Germany) and 30 Hz flicker electroretinography (ERG) were also performed. ERG results were recorded according to the International Society for Clinical Electrophysiology of Vision standard protocol recommended in 2008 using LS-C (Mayo Co., Nagoya, Japan) and Neuropack MEB-2204 systems (Nihon Kohden, Tokyo, Japan).…”
Section: Subjectsmentioning
confidence: 99%
“…4 EYS is an important and common cause of RP in the Japanese, Spanish, British, Chinese, Israelis, and Palestinians. [5][6][7][8][9] Furthermore, a report has described that EYS-associated RP patients share a relatively uniform phenotype with near-normal central visual function up to their 20s. 10 We have previously reported that severity of RP patients with EYS mutations was relatively moderate among RP patients with various mutations.…”
Section: Introductionmentioning
confidence: 99%
“…25 Several studies have proven TES as a highefficiency method of molecular diagnosis of USH, with a detection rate of around 70%. 10,[26][27][28][29] Targeted NGS can detect both point mutations and large genomic DNA rearrangements; its ability to detect CNVs is related to the coverage depth of TES. 10,26 In one Spanish study, six different CNVs of USH2A, CDH23, PCDH15, and GPR98 were detected by their own capture panel TES, with a mean coverage of 1334x.…”
mentioning
confidence: 99%